PERSENTASE PENGULANGAN FOTO RADIOGRAFI PERIAPIKAL DI RUMAH SAKIT GIGI DAN MULUT PENDIDIKAN BAITURRAHMAH - Wisnu, Fredy Rendra Taursia; Iswani, Resti; Rahmaningseh, Fitria (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2024)
Introduction: Radiographic repetition analysis is a systematic process to record the results of rejected or repeated images by determining the cause of image repetition to improve program effectiveness and quality of service in radiology installations. One method to assess the quality results of radiology services is to calculate the percentage of repeated x-rays in each month. In accordance with the Decree of the Indonesia Minister of Health Number 129 of 2008 concerning the minimum service standards of hospitals, the maximum permissible limit for errors and the repetition rate of radiology X-ray services is ≤ 2%. Objective: This study aims to determine the percentage of repetition of periapical radiographic photographs at Baiturrahmah Dental Hospital Education Center (RSGMP Baiturrahmah). Methods: This study employed a quantitative, descriptive observational methodology. A total of 454 periapical X-ray data points were collected over the period from July to October 2023 using the saturated sampling technique. The research data were analysed using Excel formulas and presented in tabular and graphical formats. Results: The highest repetition result was observed in August at 10.5%, while the lowest X-ray repetition was recorded in September at 0%. The average repetition from July to October 2023 was 6.8%. Conclusion: The highest repetition rate was observed in pediatric patients, at 14.17%, due to improper film size selection. The mandibular posterior teeth exhibited the greatest repetition rate, at 61.30%. The overall score in this research is classified as high